Identità complesse in un’Europa plurale - Garcìa Faroldi, Livia (SocietàMutamentoPolitica, 2010)
In this contribution we propose a review of the main theories on European Identity, in the field of sociology and political science: cosmopolitan, rational actor factors, national political approaches. Furthemore, the article analyses the interaction between the two level of identification. Most of the research shows that European identity is compatible with National identity. These are based on different elements: the first mainly on cultural factors, the second on instrumental factors. Findings reveal that the type of identification with the Nation and the interaction between the two identities is fundamental to understand the support of population toward European Union.